2010
DOI: 10.3928/00989134-20100330-04
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering the Art of Healing Connection by Creating the Tree of Life Poster: A Pilot Program for Hospitalized Older Adults

Abstract: The goal of this project was to provide a way for hospital staff to form meaningful therapeutic relationships with patients in the fast-paced hospital environment. Watson's Theory of Human Caring was the framework guiding the project. The Lifestory intervention was a Tree of Life poster depicting sources of encouragement and enjoyment, special memories, life lessons, family, and roots. Preintervention and postintervention measures included quality of life (QOL) and spirituality scales with established psychome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Nursing home patients’ relations to the staff nurses have occurred to be a powerful influence on patient’s meaning in life and well‐being (Hollinger‐Samson & Pearson 2000, Haugan Hovdenes 2002, Clarke et al. 2003, Finch 2006, McGilton & Boscart 2007, Heliker 2009, Pipe et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing home patients’ relations to the staff nurses have occurred to be a powerful influence on patient’s meaning in life and well‐being (Hollinger‐Samson & Pearson 2000, Haugan Hovdenes 2002, Clarke et al. 2003, Finch 2006, McGilton & Boscart 2007, Heliker 2009, Pipe et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…NH patients are in general extremely vulnerable, characterised by frailty, mortality, disability, powerlessness and dependency; hence, the relationships with the nursing staff are critical to their self‐respect, feelings of self‐worth, dignity and thereby well‐being (Clarke et al. 2003, Heliker 2009, Pipe et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As nursing home patients generally are extremely vulnerable, characterized by frailty, mortality, disability, powerlessness and dependency, interaction with professional caregivers is critical to their self-respect, feelings of selfworth, dignity and meaning-in-life (Clarke et al 2003, Heliker 2009, Pipe et al 2010, Burack et al 2012. Nursing practice comprises interwoven relational, moral and practical aspects (Martinsen 1989, N aden & Eriksson 2004, Watson 2007c where nursing care encompasses the patient's fundamental needs, as well as the patient's values and experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Other research showed a statistically significant difference from pre- to posttest in terms of styles for coping with stress and infertility impact scores in women receiving infertility treatment if they were exposed to Watson’s care; women in the experimental group developed positive coping methods (Ozan & Okumus, 2017). Another application indicated that, with the guidance from the model, elderly people’s emotional, spiritual, and physical well-being level and quality in late life significantly increased (Pipe, Mishark, Hansen, Hentz, & Hartsell, 2010). Even though the samples from this prior research differ from the current study, the common aspect is the effectiveness of the care suggested by Watson’s model.…”
Section: Discussionmentioning
confidence: 99%